Muslim Minority in China: Integration or Separation? - Elaskary, Mohamed Ibrahim; Yun, Eun Kyeong (Journal of Humanities & Social Sciences, 2021)
This paper focuses on the Muslim minority in China, their presence, integration, the challenges from which they suffer and the way to deal with such teething troubles. In this paper, we argue that Muslims in Chinese Inner Mongolia has been integrated successfully into China. Besides providing insights into their presence and well-being in China, their integration into mainstream Communist China is the focal point of interest. Muslims in China has been living as minority communities for centuries. We must emphasize here that, there will be occasions when we mention Muslims from other areas in China away from Inner Mongolia for cross-purpose contextualization. The commonly held view, especially by Western scholars, is that the Muslim populace in China has resisted their integration into Chinese society in toto. This is a fallacy that needs to be addressed. There are millions of Muslims of different sects who live across the Chinese mainland, the majority of whom have been living for ages in harmony with their fellow citizens. However, there are many grievances in the Muslim community that have existed for decades and seemingly no plausible solutions looming on the horizon. The methodology we will be using throughout this paper is the analytical-qualitative approach. Using available archival, research data as well as relevant studies and media reports, we will start by giving a general background on the geographical demographics and characteristics of the area and its people. We will move on to discussing the daily life practices of the Muslim community, such as crafts, social life, literacy and religion. Then, we will conclude by giving an overall view of the position of the Muslim community in their motherland China, how to enhance the mechanisms that can facilitate active integration into Chinese society and the extent of suffering from repression and injustice in their homeland.
Keywords: East Turkestan; Han; Hui; Minority; Xinjian; Muslims; Mongolian; Uighurs